Site-specific targeting of aflatoxin adduction directed by triple helix formation in the major groove of oligodeoxyribonucleotides. - Jones, W R (1998)
The targeted adduction of aflatoxin B1- exo -8,9-epoxide (AFB1- exo -8,9-epoxide) to a specific guanine within an oligodeoxyribonucleotide containing multiple guanines was achieved using a DNA triplex to control sequence selectivity. The oligodeoxyribonucleotide d(AGAGAAGATTTTCTTCTCTTTTTTTTCTCTT), designated '3G', spontaneously formed a triplex in which nucleotides C27*G2*C18 and C29*G4*C16 formed base triplets, and nucleotides G7*C13formed a Watson-Crick base pair. The oligodeoxyribonucleotide d(AAGAAATTTTTTCTTTTTTTTTTCTT), designated '1G', also formed a triplex in which nucleotides C24*G3*C24 formed a triplet. Reaction of the two oligodeoxyribonucleotides with AFB1-exo-8,9-epoxide revealed that only the 3G sequence formed an adduct, as determined by UV absorbance and piperidine cleavage of the 5'-labeled adduct, followed by denaturing polyacrylamide gel electrophoresis. This site was identified as G7by comparison to the guanine-specific cleavage pattern. The chemistry was extended to a series of nicked bimolecular triple helices, constructed from d(AAAGGGGGAA) and d(CnTTCTTTTTCCCCCTTTATTTTTTC5-n) (n = 1-5). Each oligomer in the series differed only in the placement of the nick. Reaction of the nicked triplexes with AFB1- exo -8,9-epoxide, piperidine cleavage of the 5'-labeled adduct, followed by denaturing polyacrylamide gel electrophoresis, revealed cleavage corresponding to the guanine closest to the pyrimidine strand nick. By using the appropriate pyrimidine sequence the lesion was positioned within the purine strand.